Analisis Kemandirian Belajar Siswa dalam Pembelajaran Tatap Muka Terbatas pada Mata Pelajaran Matematika Kelas V SD Negeri 102004 Tiga Juhar - Rista Mawati Br Tarigan; Samsul Bahri (Education & Learning, 2022)
The formulation of the problem in this study is "How is student learning independence in face-to-face learning limited to mathematics in Class V at SD Negeri 102004 Tiga Juhar with low, medium and high categories?". The research method used was descriptive qualitative. describes the independence of student learning in face-to-face learning is limited to mathematics. The subjects in this study were SD Negeri 102004 Tiga Juhar fifth grade students, totaling 25 students. Collecting data in interpreting the data in the study obtained from questionnaires and interviews. Qualitative data in this study were obtained from data reduction, data presentation and conclusion drawing. moderate learning by 36%. Learning independence is high at 24%. There are several factors that influence each indicator of learning independence, including the lack of utilizing and finding relevant sources and the lack of self-initiative.